Impact of Dimensions of Brand Equity in Purchasing Financial Products: An Empirical Study on Islami Bank Bangladesh Limited - Fatema, Mohsina; Azad, Md. Abul Kalam; Fatema, Nazneen (Asian Accounting and Auditing Advancement, 2014)
This study aims at examining different dimensions of practicality and applications of customer-based brand equity using Aaker’s five-factor model. A structured questionnaire was filled from a sample of 645 actual account holders (customers) of Islami Bank Bangladesh Ltd. Exploratory Factor Analysis is used to investigate the causal relationships among the proposed seven dimensions of brand equity. This paper is surveyed within Dhaka city. Brand Image is found to be the most significant latent variable in the measurement of brand equity dimensions. Brand Association and Brand Loyalty are found to be influential dimensions of brand equity. Weak support for the perceived quality and brand awareness dimensions are identified in this paper.